The effect of a multidirectional functional load by means of OFP on the indicators of systemic hemodynamics and vegetative support of qualified boxers - Neupokoev S.N.; Shilko V.G.; Guseva N.L.; Katkov V.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to influence of multidirectional functional load by means of general physical training on the indicators of systemic hemodynamics and autonomic support of qualified boxers. Methods and structure of the study. Two equal groups of 1st category boxers from 18 to 20 years old, 15 people in each group, were formed: experimental group (EG) and control group (CG). All athletes were represented in the weight category up to 71 kg. Results and conclusions. Multidirectional means of functional training for indicators of systemic hemodynamics and autonomic support of the body of qualified boxers have been identified. During testing, the fact was recorded that the use of general physical training tools, which largely involve the muscles of the lower extremities in the activity, contributes to the adequate development of optimal functional training in boxing, which is qualitatively reflected in the indicators of systemic hemodynamics and autonomic support of the athletes body in response to the work performed.